ANALISIS KONDISI FISIK PEMAIN SEPAK BOLA USIA 15 TAHUN DI SSB BOCAH JUNIOR TANJUNG JABUNG BARAT - M.Sutiyoso; Hendri Munar; Bangkit Yudho Prabowo (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the physical condition of 15-year-old soccer players at SSB Bocah Junior Tanjung Jabung Barat. The physical condition of players is crucial to team success, especially at the adolescent age, which is an important phase in the development of both physical and technical skills. This research uses a descriptive method with a quantitative approach to evaluate the players' speed, agility, and anaerobic endurance (VO₂Max). The results show that most players' physical conditions need improvement, particularly in speed and endurance. Only a few players demonstrate good physical condition, while the majority fall into the less optimal categories in speed and endurance tests. The study suggests the need for a more structured training program to improve the less optimal physical components, especially anaerobic endurance and speed.